Depreciation charges as a source of fixed assets renewal - N. Z. Zotikov (Вестник университета)
Normal functioning of any industrial enterprise significantly depends on the technical equipment of production. Low investment activity of economic entities, which in recent years contributed to a high degree of physical and moral depreciation of fixed assets, in the conditions of reduced opportunities for public investment due to the sanctions, limited credit availability, and high rates of the Bank of Russia strengthen the role and importance of own sources of economic entities in fixed assets reproduction process. The relevance of the issue increases in conditions of high level of fixed assets depreciation in commercial organizations and reduction of fixed assets renewal ratio. The subject of the study is the regional depreciation policy assessment. The purpose of the study is to identify the directions and possibilities of effective amortization policy to ensure fixed assets reproduction. Such research methods as analysis and synthesis, grouping, generalization, comparison, tabular, etc. were used. The present study is based on the official data of the Federal State Statistics Service and the Federal Tax Service. It has been established that the regions have a high degree of fixed assets depreciation, extremely low rate of their renewal, and a small share of amortization charges in the costs. The methods of fixed assets depreciation provided for by Chapter 25 of the Tax Code of the Russian Federation as investment sources formation are underused.